Об устройстве каменной гробницы в кургане Карагодеуашх - Вахтина, М.Ю. (Археологія і давня історія України, 2018)
Статья посвящена особенностям планировки
каменной гробницы, открытой в 1888 г. в кургане
Карагодеуашх в Прикубанье. В устройстве гробницы, как и в ее вещевом комплексе, нашли отражение
основные «векторы» контактов элиты Боспора и тесно связанной с ней варварской аристократии. The article deals with the planning of the stone vault
in Karagodeuashkh mound, excavated by E. F. Felitzin
in 1888 in Kuban’ area. The mound contained «rich»
burials of the representatives of sindae-maeotian aristocracy
and dated to 330—315 BC. The construction
of Karagodeuashkh vault shows parallels to enfilade
crypts which were wide spread during that time at the
territory of ancient Thracia. The finds of metal objects in the inventory of the burial complexes testify to contacts
with Thracia and Northern Greece. The materials of Karagodeuashkh mound seem to be important for
the examining of cultural contacts of Bosporan kingdom and its Hellenized barbarian periphery in the last
third of the 4th century BC. The analysis of the burial goods and construction of the mound is also of great importance
for the study of the ideology of the local tribes of Kuban region.